Financial Devlopment, Environmental Quality, Trade and Economic Growth: What Causes What in MENA Countries? - Anis Omri; Saida Daly; Christophe Rault; Anissa Chaibi (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper examines the relationship between financial development, CO2 emissions, trade and economic growth using simultaneous-equation panel data models for a panel of 12 MENA countries over the period 1990-2011. Our results indicate that there is evidence of bidirectional causality between CO2 emissions and economic growth. Economic growth and trade openness are interrelated i.e. bidirectional causality. Feedback hypothesis is validated between trade openness and financial development. Neutrality hypothesis is identified between CO2 emissions and financial development. Unidirectional causality running from financial development to economic growth and from trade openness to CO2 emissions is identified. Our empirical results also verified the existence of environmental Kuznets curve. These empirical insights are of particular interest to policymakers as they help build sound economic policies to sustain economic development and to improve the environmental quality.
Keywords: E44; E58; F36; P26; 330; financial development; CO2 emissions; trade; economic growth; simultaneous-equation models